2012
DOI: 10.1521/pedi.2012.26.2.238
|View full text |Cite
|
Sign up to set email alerts
|

Childhood Abuse in Chinese Patients with Borderline Personality Disorder

Abstract: This study examined (1) the relative prevalence of childhood abuse and other pathological childhood experiences in China reported by outpatients with borderline personality disorder (BPD), with other personality disorders, and without personality disorders; and, (2) whether the primary predictors of BPD in North America are associated with the development of BPD in China. The childhood experiences of 203 outpatients with BPD, 109 outpatients with other personality disorders, and 70 outpatients without Axis II … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
2
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 44 publications
1
16
2
2
Order By: Relevance
“…In particular, the highest associations were found for specific types of emotional abuse (parental antipathy and neglect) and for sexual abuse. This is in line with previous research findings (Haugaard, 2004;Huang et al, 2012;Paris, 2000;Venta et al, 2012;Zweig-Frank & Paris, 1991).…”
Section: Bpd and Childhood Maltreatmentsupporting
confidence: 93%
“…In particular, the highest associations were found for specific types of emotional abuse (parental antipathy and neglect) and for sexual abuse. This is in line with previous research findings (Haugaard, 2004;Huang et al, 2012;Paris, 2000;Venta et al, 2012;Zweig-Frank & Paris, 1991).…”
Section: Bpd and Childhood Maltreatmentsupporting
confidence: 93%
“…It has previously been suggested that multiple types of childhood trauma (e.g. emotional, physical and sexual abuse) are significant predictors of borderline PD (Huang et al 2012) with reports that experiencing physical abuse and neglect, but not CSA are risk factors for the development of borderline PD (Widom et al 2009). Taken together, these findings suggest that the aetiology of borderline PD is very complex and involves, in addition to possibly genetic and biological factors, several psychosocial factors including perhaps multiple childhood trauma experiences and not just CSA alone (Joyce et al 2003;Huang et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…More recent findings have, however, suggested that multiple types of childhood trauma (e.g. emotional, physical and sexual abuse) may be significant predictors of borderline PD (Huang et al 2012) with some studies suggesting that physical abuse or neglect, may potentially have a more significant aetiological role for the development of borderline PD than CSA (Widom et al 2009). …”
Section: Introductionmentioning
confidence: 99%
“…¿Acaso estos individuos informan el abuso que han experimentado con exactitud? (ver Battle et al, 2004;Huang et al, 2012;Machizawa-Summers, 2007;Zanarini et al, 2000). Es decir, muchas de estas críticas están en el nivel de afirmaciones de abuso sexual o físico.…”
Section: Desconfianza Epistémica Y El Motivo Para La Intensificada VIunclassified
“…Los resultados obtenidos en los estudios de cohorte longitudinal confirmaron los hallazgos de estudios transversales de que la negligencia emocional y el abuso predicen la aparición de síntomas de TLP más tarde en la vida (Carlson, Egeland, & Sroufe, 2009 La significación específica de la negligencia y el abuso emocional para el TLP es enfatizada en los estudios que fallaron en encontrar una diferencia significativa en relación con el abuso sexual (Bellino et al, 2005;Bierer et al, 2003;Laporte, Paris, Guttman, & Russell, 2011;Widom et al, 2009;Zanarini et al, 2000) o abuso físico (Battle et al, 2004;Widom et al, 2009 (solo en pacientes masculinos) Wingenfeld et al, 2011) aun así revelaron un significativo incremento en la prevalencia del TLP asociado con negligencia emocional y abuso. En tres estudios (Gratz, Tull, Baruch, Bornovalova, & Lejuez, 2008;Huang et al, 2012;Machizawa-Summers, 2007), la negligencia emocional y el abuso fueron predictores significativos de los síntomas de TLP por encima o por debajo de otros tipos de abuso. En el estudio de Specht, Chapman y Celucci (2009), la falta de apoyo emocional mostró ser el único predictor significativo para los síntomas de TLP.…”
Section: Desconfianza Epistémica Y El Motivo Para La Intensificada VIunclassified